233 Estrus Response and Pregnancy Rates of Beef Replacement Heifers Enrolled in Two Fixed-time Artificial Insemination Protocols, with or Without Pre-synchronization. (8th October 2021) - Mercadante, Vitor R G Rodrigues Gomes; Lamb, G Cliff C; Oosthuizen, Nicky; Wege Dias, Nicholas W; Pancini, Stefania; Haines, Hannah; Currin, John; Clark, Sherrie; Stewart, Jamie L; Pent, Gabriel J; Holton, Matthew P; Davis, Dylan B; et al.
Abstract: Pre-synchronization strategies with prolonged exposure to exogenous progesterone have the potential to alter estrus expression and improve fertility in replacement beef heifers. The objective of this study was to evaluate the estrus response and pregnancy rate of beef heifers enrolled in two fixed-time artificial insemination (TAI) protocols. A total of 306 heifers (14 ± 2 months of age; 372 ± 24 kg body weight [BW]) at three locations were enrolled in the study. Within location, heifers were stratified by age and BW and randomly assigned to one of two treatments: 1) PG-CIDR54 (n = 152), heifers were administered prostaglandin F2α (PGF; 25 mg) and a controlled internal drug releasing (CIDR) insert (Day -14), an injection of GnRH [100 μg (Day -7)], PGF injection and CIDR removal (Day 0), and a second injection of GnRH concurrently with TAI 54 ± 2 h later (Day 2); 2) 7-day CO-Synch+CIDR (CTRL; n = 154), heifers were administered GnRH (100 μg) and a CIDR insert (Day -7), PGF (25 mg) injection and CIDR removal (Day 0), and a second injection of GnRH concurrently with TAI 54 ± 2 h later (Day 2). All heifers received an estrus alert patch on Day 0 and were evaluated for patch activation at TAI on Day 2. Pregnancy was diagnosed by transrectal ultrasonography between 35 and 55 days after TAI. The percentage of heifers exhibiting estrus between Day 0 and 2 was greater (P < 0.01) in PG-CIDR54 compared with CTRL (77.0 and 39.6%, respectively). In addition, pregnancy rate to TAI tended (P = 0.08) to be greater for PG-CIDR54 compared with CTRL (48.0 and 38.3%, respectively). We conclude that beef heifers enrolled in the PG-CIDR54 protocol had increased estrus expression and tended to have greater pregnancy rate when compared with heifers enrolled in the 7-day CO-Synch+CIDR protocol.